2022
DOI: 10.3389/fnut.2021.797801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Barley Starch Contents on the Performance, Nutrient Digestion, Rumen Fermentation, and Bacterial Community of Fattening Hu Sheep

Abstract: The objective of this experiment was to investigate the effects of substituting corn starch (CS) with barley starch (BS) on the growth performance, nutrient digestion, rumen fermentation, and bacterial community of fattening Hu sheep. Seventy-two Hu lambs with similar initial body weight (BW, 29.70 ± 1.70 kg) were randomly assigned to four treatments, with 18 lambs per group. The four experimental diets have identical starch contents but with different starch sources as 100% starch from corn (BS-0), 33% starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…These results indicated that a high barley starch level in the diet promoted the proliferation of amylolytic bacteria, but the abundances of pH-sensitive bacteria decreased. Compared with the previous study by Ma et al [ 8 ], more differences in the microflora of the rumen were observed in this trial. The reason for the differences between these studies could be due to the different animals, with fattening sheep of a similar age (about 3 months) and initial BW (29.70 ± 1.70 kg) used in the former, while fistula sheep of about 10 months age and an initial BW of 53.78 ± 3.14 kg were used in our study.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…These results indicated that a high barley starch level in the diet promoted the proliferation of amylolytic bacteria, but the abundances of pH-sensitive bacteria decreased. Compared with the previous study by Ma et al [ 8 ], more differences in the microflora of the rumen were observed in this trial. The reason for the differences between these studies could be due to the different animals, with fattening sheep of a similar age (about 3 months) and initial BW (29.70 ± 1.70 kg) used in the former, while fistula sheep of about 10 months age and an initial BW of 53.78 ± 3.14 kg were used in our study.…”
Section: Discussioncontrasting
confidence: 92%
“…However, barley has a higher amylopectin content than corn, which can be fermented and digested in the rumen to a greater extent than corn and could be a potential replacement for corn as a source of energy for ruminants [ 5 , 6 ]. Combining barley starch (BS) with corn starch (CS) could improve the efficiency of starch digestion by balancing starch fermentation in the rumen or small intestine [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high-energy dietary formulation alters the rumen micro-ecosystem accordingly, leading to improvements in performance traits [ 10 ]. Feeding fattening Hu sheep a high-concentrate corn-based diet improves the performance and rumen fermentation indexes [ 11 ]. There are sophisticated exchanges between ruminants and rumen microorganisms.…”
Section: Introductionmentioning
confidence: 99%